Changing Boycott into Reconciliation: A Discourse Analysis of Product Advertisements to Strengthen Image Recovery Strategies - Asyaidir, Muthia Balqis; Rachmy, Rezha Mardianty; Amalia, Fiqih (Universitas Islam Negeri Raden Intan Lampung, 2024)
This article examines product advertisements from companies affected by public boycotts as a form of support for the Palestinian people, for companies originating from countries supporting bomb attacks carried out by Israel. Viewed from a discourse analysis perspective, with a focus on the use of symbols, both verbal and non-verbal, in advertising to improve the image of PT. Unilever Indonesia and the strategies advertisers use to influence their customers. This research uses a qualitative approach method, while its type uses a media representation approach and Teun Van Dijk's discourse analysis. The discourse built in PT. Unilever Indonesia on television has a big influence on the audience in improving its image. Advertising shows that contain symbols to build an image that is broadcast in verbal and non-verbal form. Verbal symbols are symbols that use language, spoken or written, while non-verbal symbols are symbols that can be in the form of pictures, clothing, smiling faces and movements. The research results show that advertisers not only improve their image, but while promoting products they also highlight the ethical standards, social and cultural values of Indonesian society, and how TV advertising has shaped ideology in the practice of social life in Indonesia.